Implementasi Pengelolaan Dana Bos untuk Meningkatkan Transparansi dan Akuntabilitas Sekolah - Aprilistia Nugraheni; Della Aprilyana; Diah Puri Widyawati; Tasya Putri; Dinda Zahra Umammi; Bayu Purbha Sakti (CV. ITTC INDONESIA, 2026)
Quality education in Indonesia continues to face challenges in public fund management, particularly the School Operational Assistance (BOS) program. Key problems include limited managerial understanding of regulations, low fund-use transparency, weak accountability, and financial administration constraints that impede program effectiveness. This article aims to analyze BOS fund management implementation in improving school transparency and accountability, while formulating systematic improvement strategies applicable to Indonesian schools. The study employs a library research method reviewing 20 scientific sources comprising national journals, reference books, and official regulations published between 2018 and 2024, with inclusion criteria focused on relevance to BOS fund management, transparency, and school accountability. The analysis was conducted through systematic identification, classification, and content interpretation. Results indicate that BOS fund management success is influenced by three key factors: human resource competence, principal leadership, and school committee participation. Recommended strategies include periodic competency training, strengthening transparency through digital publication, enhancing accountability through systematic documentation, periodic monitoring and evaluation, and adoption of information technology in financial administration. Through these strategies, transparent and accountable BOS fund management can support effective, professional school governance oriented toward educational quality improvement